Efficacy of Dexamethasone on Pain and Swelling Following Extraction of Impacted Mandibular Third Molars - Saber Mizher (Dentistry 3000)
Objective: Surgical extraction of impacted mandibular third molars is a common dental procedure associated with significant postoperative complications, including pain and swelling. Dexamethasone, a corticosteroid known for its anti-inflammatory properties, has been utilized to mitigate these postoperative sequelae. This study aimed to evaluate the efficacy of submucosal dexamethasone injection in reducing postoperative pain and swelling compared to a control group receiving normal saline. Material and Methods: A randomized controlled trial was conducted involving 40 patients scheduled for surgical extraction of impacted mandibular third molars. Participants were randomly assigned to two groups: the study group received a submucosal injection of 8mg dexamethasone, while the control group received an equivalent volume of normal saline. Postoperative pain was assessed using a Numeric Rating Scale (NRS) at 24 hours, 48 hours, and 7 days post-surgery. Facial swelling was measured at the same intervals using standardized landmarks. Results: The results indicated that the study group experienced significantly less pain at 24 hours (NRS: 4.28 ± 0.71 vs. 5.8 ± 0.87, p=0.001) and 48 hours (NRS: 3.45 ± 0.75 vs. 4.9 ± 0.99, p=0.001) compared to the control group. Additionally, facial swelling was significantly reduced in the dexamethasone group at 48 hours (3.01% vs. 6.49%, p=0.001). By the 7th postoperative day, both groups showed similar levels of pain and swelling, indicating that the effect of dexamethasone was most pronounced in the early postoperative period. Conclusion: Submucosal injection of dexamethasone is effective in minimizing postoperative pain and swelling following the surgical extraction of impacted mandibular third molars. The findings support the use of dexamethasone as a standard adjunctive treatment in oral surgery to enhance patient recovery during the critical early postoperative phase. Further studies are warranted to explore optimal dosing and long-term outcomes associated with this intervention.